Hydrogen-diesel dual fuel combustion in a direct injection diesel engine. (1st January 2011) - Saravanan, N.; Nagarajan, G.
Hydrogen is expected to be one of the most important fuels in the near future to meet the stringent emission norms. Hence in the present study, the combustion of hydrogen-diesel duel fuelled engine was investigated. Hydrogen was injected in the intake port during the suction stroke and diesel was injected inside the combustion chamber near TDC. The start of injection for hydrogen was maintained at 5° BGTDC and the duration of the injection was maintained at three different periods of 30°, 60°, and 90° crank angles with different hydrogen injection flow rates, 2 lpm, 3.5 lpm, 5.5 lpm, 7.5 lpm and 9.5 lpm. The result shows that the hydrogen injection duration of 30° crank angles and flow of 7.5 lpm gives higher brake thermal efficiency by about 8%. Smoke emissions decrease by 60% and NO X emission increase by 3% at optimised full load condition.